2017
DOI: 10.21873/cgp.20059
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Gene Sequencing of Gallbladder Carcinoma Identifies High-impact Somatic and Rare Germline Mutations

Abstract: Abstract. Background: Gallbladder carcinoma (GBC) isGallbladder carcinoma (GBC) is a type of biliary tract cancer, characterized by rapid progression and high mortality. Significant risk factors for GBC include presence of gallstones, chronic inflammation, anomalous pancreatobiliary ductal junctions, advancing age and female gender (1).Incidence and prevalence of GBC exhibit remarkable ethnic and geographical variability. This variability has been attributed to genetic predisposition and lifestyle habits or en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
(63 reference statements)
0
10
0
Order By: Relevance
“…Those studies have shown that the most frequently altered genes in GBC are TP53, CDKN2A/B, ARID1A, ERBB2, and PI3KCA [113][114][115][116][117]. Some series have also reported KRAS [113,115] and SMAD4 [115,118] as commonly mutated genes in this neoplasia. Recently, Wardell et al investigated somatic and germline mutations in 412 BTCs from Japanese and Italian populations, which included 66 gallbladder or cystic duct cancers.…”
Section: Molecular Prognostic Biomarkersmentioning
confidence: 96%
“…Those studies have shown that the most frequently altered genes in GBC are TP53, CDKN2A/B, ARID1A, ERBB2, and PI3KCA [113][114][115][116][117]. Some series have also reported KRAS [113,115] and SMAD4 [115,118] as commonly mutated genes in this neoplasia. Recently, Wardell et al investigated somatic and germline mutations in 412 BTCs from Japanese and Italian populations, which included 66 gallbladder or cystic duct cancers.…”
Section: Molecular Prognostic Biomarkersmentioning
confidence: 96%
“…The definition of RTPS specifies the presence of multiple Rhabdoid tumors and molecular identification of a germline heterozygous pathogenic variant allele, either SNF5 or SMARCA4 (Brg-1) (13). Thus, it has been indicated that significant genes for tumor development exist not only in somatic mutatiosn but also in germline mutations (37). In our patient, a point-mutation in exon 2 of the SNF5 gene (c.157 C>T) was identified as a germline mutation.…”
Section: Discussionmentioning
confidence: 62%
“…We achieved deep sequencing coverage and identified pathogenic alterations in 95.2% (20/21) of the patients with BTC using EUS-FNA samples. Previous reports on BTC showed equal or inferior success rates (47.5%, 92.1%, and 90.1%) (1618) in identifying somatic alterations in BTC specimens obtained through surgical resection or ETB. With regard to using Hotspot Cancer Panel with pulmonary and pancreatic tissue specimens obtained through EUS-FNA, previous reports have shown 61.7%, 50%, and 100% success rates for the analysis of somatic alterations using TAS (10,19,20).…”
Section: Discussionmentioning
confidence: 88%